2021
DOI: 10.1111/tpj.15204
|View full text |Cite
|
Sign up to set email alerts
|

NOL‐mediated functional stay‐green traits in perennial ryegrass (Lolium perenne L.) involving multifaceted molecular factors and metabolic pathways regulating leaf senescence

Abstract: SUMMARY Loss of chlorophyll (Chl) is a hallmark of leaf senescence, which may be regulated by Chl catabolic genes, including NON‐YELLOW COLORING 1 (NYC1)‐like (NOL). The objective of this study was to determine molecular factors and metabolic pathways underlying NOL regulation of leaf senescence in perennial grass species. LpNOL was cloned from perennial ryegrass (Lolium perenne L.) and found to be highly expressed in senescent leaves. Transient overexpression of LpNOL accelerated leaf senescence and Chl b deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 73 publications
3
28
0
Order By: Relevance
“…Specifically, the identification of important stay-green mutants unmasked the key catalyzing steps in the chlorophyll breakdown pathway. In brief, the breakdown of chlorophyll was started with the conversion of chlorophyll b (Chl b ) to Chl a catalyzed by two Chl b reductase paralogous, NYC1 and NOL ( Yu et al, 2021 ). Next, magnesium was released from Chl a by the STAY-GREEN protein (SGR) to yield pheophytin a ( Shimoda et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the identification of important stay-green mutants unmasked the key catalyzing steps in the chlorophyll breakdown pathway. In brief, the breakdown of chlorophyll was started with the conversion of chlorophyll b (Chl b ) to Chl a catalyzed by two Chl b reductase paralogous, NYC1 and NOL ( Yu et al, 2021 ). Next, magnesium was released from Chl a by the STAY-GREEN protein (SGR) to yield pheophytin a ( Shimoda et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms of LpNOL regulating leaf senescence and controlling the functional stay-green phenotype in perennial ryegrass were reported in a previous study (Yu et al, 2021). While the mechanisms by which NOL regulates leaf senescence are yet not completely understood, NOL-mediated leaf senescence has been associated with positive regulation of Chl b degradation due to its role as Chl b reductase (Sato et al, 2010;Yu et al, 2021). In this study, metabolic profiling of perennial ryegrass with LpNOL knockdown found that five metabolites (valine, malic acid, threonic acid, shikimic acid, and chlorogenic acid) were uniquely upregulated in LpNOL-knockdown plants exposed to heat stress, and six metabolites (aspartic acid, glutamic acid, 5-oxoproline, senescence could be related to the activation of amino acid and organic acid metabolism (Figure 9) in addition to its previously reported function in the catalytic breakdown of Chl degradation (Yu et al, 2021).…”
Section: Discussionmentioning
confidence: 72%
“…The enhancement of Chl content, F v /F m , Pn, and cell membrane stability suggest that knockdown of LpNOL suppressed heat-induced leaf senescence. The molecular mechanisms of LpNOL regulating leaf senescence and controlling the functional stay-green phenotype in perennial ryegrass were reported in a previous study (Yu et al, 2021). While the mechanisms by which NOL regulates leaf senescence are yet not completely understood, NOL-mediated leaf senescence has been associated with positive regulation of Chl b degradation due to its role as Chl b reductase (Sato et al, 2010;Yu et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Then, 7-HMChl a is transferred to Chl a by 7-hydroxymethyl Chl a reductase (HCAR) [ 14 ]. However, the Chl cycle is more than a reciprocal conversion of Chl a and Chl b ; it also plays an important role in the degradation of light-harvesting Chl a / b protein complex of photosystem II (LHCII) [ 15 , 16 ]. Arabidopsis SGR1 physically interacts with the Chl catabolic enzymes (CCEs) and LHCII, forming a multi-protein complex that is likely important for rapid detoxification of Chl catabolic intermediates in senescing chloroplasts [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%